2022
DOI: 10.1108/jfm-05-2022-0055
|View full text |Cite
|
Sign up to set email alerts
|

Management psychological characteristics and earnings management

Abstract: Purpose This study investigates the relationship between management's psychological characteristics (managers' narcissism, overconfidence and managers' myopia) and earnings management in the pre-Islamic State of Iraq and Syria (ISIS) and post-ISIS eras. Design/methodology/approach A multivariate regression model was used to test the hypotheses. The research hypotheses were tested using a sample of all companies listed on the Iraqi Stock Exchange from 2014 to 2020. Findings Findings indicate a positive and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 105 publications
0
6
0
Order By: Relevance
“…Furthermore, quarterly data can be used to better understand the association between COVID-19 crisis and EM. Finally, as managerial psychological characteristics may influence EM [ 68 , 69 ], the impact of the pandemic on managerial psychology and its relationship to EM may be of interest to future research.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, quarterly data can be used to better understand the association between COVID-19 crisis and EM. Finally, as managerial psychological characteristics may influence EM [ 68 , 69 ], the impact of the pandemic on managerial psychology and its relationship to EM may be of interest to future research.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative REM metrics include abnormal cash flow from operating activities, abnormal discretionary expenses, and abnormal production costs. In the calculation of REM, abnormal discretionary expenditure and abnormal operating cash flows should be multiplied by negative one (Potharla, 2022; Salehi et al., 2022; Zang, 2012), so that higher REM indicates more REM activities manipulation. To determine whether our results are robust with respect to this alternative measure, we repeat the processes of selecting the most appropriate model and testing the multicollinearity, autocorrelation, and heteroscedasticity problem.…”
Section: Empirical Analysis and Discussionmentioning
confidence: 99%
“…For such reasons, REM reduces the informativeness of current earnings and makes earnings less persistent over time (Grahama et al, 2005;Li, 2019;Mizik, 2010;Roychowdhury, 2006). Similarly, Salehi et al (2022) demonstrate that REM is related to management myopia, thereby REM negatively affecting performance in long-term.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 90%
See 1 more Smart Citation
“…Azad et al (2023) reported a negative (positive) association between identified and modified misstatements of total assets (liabilities) and earnings management. Salehi et al (2022) argued that the psychological characteristics of a CEO proxied by IJAIM 32,2 narcissism lead to earnings management. Consistently, extant corporate governance and accounting research evidence that board independence improves corporate disclosure (Tang et al, 2013), enhances a firms' internal control mechanism (Chen et al, 2017), reduces DACC (Ye, 2014;Liu and Sun, 2021) and improve firm performance (Luan and Tang, 2007;Masulis and Mobbs, 2014).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%